COMMUNITY EMPOWERMENT BASED ECOTOURISM VILLAGE DEVELOPMENT STRATEGY IN THE NEW NORMAL ERA IN SABANG REGENCY - Hilmi Hilmi; Dy Ilham Satria (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
This study aims to determine the resources that have the potential to be developed into ecotourism in the coastal area of Sabang Regency, to determine the physical and social carrying capacity of the coastal area of Sabang to tourism activities, to formulate a model of ecotourism development based on Community Empowerment that is appropriate for managing the coastal area of Weh Island. Qualitative descriptive methods were used in determining the physical carrying capacity, surveys of community perceptions with respondents of local resident Sabang and surveys of visitor satisfaction to obtain information and analyze tourism potential in the City of Sabang and feasibility for ecotourism development. The results obtained from natural resources of marine tourism have the potential to be developed into ecotourism in the coastal area of the city of Sabang, especially in Iboh Beach, Rubiah Island, and Sumur Tiga Beach. The physical and social support capacity of the coastal area of Sabang for tourism activities is very good, so it deserves to be a national and international mainstay tourism with the concept of empowering the existing community by continuing to promote, improve and add tourism supporting infrastructure, and add national and international events in Sabang.